Development of bi-axial preferred orientation in epitaxial NiMnGa thin films and its consequence on magnetic properties. (July 2016) - Sharma, Amit; Mohan, S.; Suwas, Satyam
Abstract: In the present work, the crystal structure, the micro-structure and the crystallographic orientation of NiMnGa thin films fabricated on a Si (100) substrate using magnetron sputtering at elevated temperatures have been evaluated. X-ray diffraction based measurements confirm both in-plane and out of plane (bi-axial) alignment of the unit cells in the films. Three levels of hierarchy in the microstructure, and the presence of primary nano-twinned martensitic variants and secondary nano-twins within the primary nano-twins due to adaptive modulation are some of the important microstructural features observed in the films using a transmission electron microscope. The results of temperature-dependent magnetization measurements and in-situ high temperature X-ray diffraction experiments indicate the presence of a pre-martensite phase above room temperature. Low temperature X-ray diffraction measurements reveal the evolution of a non-modulated (NM) martensite phase at 123 K. High resolution scanning electron microscopy (FE-SEM) and high resolution X-ray diffraction measurements have been carried out for an in-depth examination of the microstructure, growth morphology and crystalline quality of the films. Graphical abstract: